Effectiveness of a blended mobile-based lifestyle intervention in women with glucose intolerance after a recent history of gestational diabetes (MELINDA): a 1-year, prospective, multicentre, randomised controlled trialResearch in context - Caro Minschart; Nele Myngheer; Toon Maes; Christophe De Block; Inge Van Pottelbergh; Pascale Abrams; Wouter Vinck; Liesbeth Leuridan; Sabien Driessens; Chantal Mathieu; Jaak Billen; Christophe Matthys; et al. (EClinicalMedicine, 2024)
Summary: Background: Women with glucose intolerance after gestational diabetes mellitus (GDM) are at high risk to develop type 2 diabetes. Traditional lifestyle interventions in early postpartum have limited impact. We investigated the efficacy of a blended mobile-based lifestyle intervention in women with glucose intolerance after a recent history of GDM. Methods: Prospective, double-arm, non-masked, multicentre randomised controlled trial (RCT) in which women with glucose intolerance, diagnosed 6–16 weeks after a GDM-complicated pregnancy, were assigned 1:1 to a one-year blended-care, telephone- and mobile-based lifestyle program (intervention) or usual care (control). Primary endpoint was the proportion of women able to achieve their weight goal (≥5% weight loss if prepregnancy BMI ≥ 25 kg/m2 or return to prepregnancy weight if prepregnancy BMI < 25 kg/m2) in the intention-to-treat sample. Key secondary outcomes were frequency of glucose intolerance, diabetes and metabolic syndrome, and lifestyle-related outcomes assessed with self-administered questionnaires. The study was registered in ClinicalTrials.gov (NCT03559621). Findings: Between April 10th 2019 and May 13th 2022, 240 participants were assigned to the intervention (n = 121) or control group (n = 119), of which 167 (n = 82 in intervention and n = 85 in control group) completed the study. Primary outcome was achieved by 46.3% (56) of intervention participants compared to 43.3% (52) in the control group [odds ratio (OR) 1.13, 95% confidence interval (CI) 0.63–2.03, p = 0.680; risk ratio 1.07, 95% CI (0.78–1.48)]. Women in the intervention group developed significantly less often metabolic syndrome compared to the control group [7.3% (6) vs. 16.5% (14), OR 0.40, CI (0.22–0.72), p = 0.002], reported less sedentary behaviour and higher motivation for continuing healthy behaviours. In the intervention group, 84.1% (69) attended at least eight telephone sessions and 70.7% (58) used the app at least once weekly. Interpretation: A blended, mobile-based lifestyle intervention was not effective in achieving weight goals, but reduced the risk to develop metabolic syndrome. Funding: Research fund of University Hospitals Leuven, Novo Nordisk, Sanofi, AstraZeneca, Boehringer-Ingelheim, Lilly.